METHODS OF CONTROLLING THE TECHNICAL-TACTICAL PREPARATION OF YOUNG FOOTBALL PLAYERS - Jorayev I. U. (Web of Journals Publishing, 2024)
The modern level of development of young football players requires many changes in the process of improving technical and tactical methods, which are closely related to the manifestation of special physical qualities and, in particular, to the level of their speed-strength training.
Keywords: Modern football, top class, technique and tactics, central striker, pedagogical observation, sprinter running.